The influence of randomness on goals in football decreases over time. An empirical analysis of randomness involved in goal scoring in the English Premier League - Wunderlich, F.; Seck, A.; Memmert, D. (Journal of Sports Sciences, 2021)
Performance analysis in football predominantly focuses on systematic contributions to success, thus neglecting the role of randomness. The present paper pursues a direct approach to quantify and analyse randomness in football by identifying random influences in the goal scoring process. The dataset includes all matches from the seasons 12/13 to 18/19 of the English Premier League, adding up to a total of 7,263 goals, that were checked for the occurrence of six variables of random influence. Additionally, the influence of nine situational variables was investigated. Results show that randomness was present for almost 50% of all goals. Moreover, it was demonstrated that the proportion of random goals decreased over the seven seasons (p < .001), is more pronounced for weaker teams (p < .05) as well as if the current scoreline is a draw (p < .05) and depends on the match situation (open play, freekick, corner, penalty). An improved understanding of randomness in football has important implications for both researchers and practitioners. Performance analysts should acknowledge randomness as a crucial factor to distinguish clearly between performance and success. Coaches could even consider the conscious creation of uncontrollable situations as a possible tactic to provoke random influences on goal scoring.